The Effect of ProblemBased Learning on Nursing Students Learning Level - Masome Modanloo; Homeira Khoddam; Shohre Kolagaree; Farideh Bastani; Sorur Parvizi; Habib Abdollahi (Kerman University of Medical Sciences, 2010)
Background & Objective: To offer a better care in complex clinical environments and with rapid changes in technology nurses need to improve their problemsolving skill Studentcentered and active learning approaches are more effective in this regard Hence this study was to determine the effect of ProblemBased Learning (PBL) on nursing students learning level Methods: This quasiexperimental study was conducted on 32 nursing students (in their fifth semester) who had chosen mental health course in Golestan University of Medical Sciences in 2007 The students were randomly divided into two groups of cases (8 persons) and controls (24 persons) Having applied PBL and lecture during the course learning was evaluated via theoretical exams of similar content and cognitive level in two groups right at the end and two months after the course Data was analyzed using MannWhitney and independent t Test The level of significance was 005 Results: Most of the students with a mean ( ± SD) age of 2185(±197) years were single (9062%) and lived in a dormitory (75%) Although the mean scores were higher in cases compared to the controls two months after the course there was no significant difference in both groups regarding overall learning However a significant difference was seen in different cognitive levels (P